English Teachers’ Perception of Using Rewards in the Classroom at a Public Elementary School in Jambi - Raninsah, Rezeki; Volya, Duti; Safitri, Nyimas Triyana; Hadiyanto, Hadiyanto; Abrar, Mukhlash (Langue (Journal of Language and Education), 2025)
This study portrayed the English teachers' perceptions of using rewards in teaching English at the elementary school level. It aimed to investigate why English teachers use rewards in their teaching. The study employed a qualitative research approach, with data collected through interviews. It was conducted at a public elementary school in Jambi, where three English teachers from the school were selected as participants, and the data was gathered through interviews. The findings illustrated a gap between teachers' theoretical understanding and their practice in implementing rewards as a way to motivate students to learn. The results showed that teachers do partially understand the concept of 'reward' in theory. In line with these findings, the study revealed that rewards can help improve several aspects of student learning, such as self-confidence, motivation, and enthusiasm for learning. The study also includes several recommendations for stakeholders and other teachers.